(untitled) (Journal of Engineering, 2024)
The two-dimensional, incompressible, and turbulent boundary layer flow over a flat plate with suction or blowing from a spanwise slot is examined numerically. The mathematical modeling involves the derivation of the governing partial differential equations of the problems. These are the continuity, the momentum, the energy and the (K-ε) turbulence model. Besides, the perfect gas law is also used. A numerical solution of the governing equations is approximated by using a finite volume method, with staggered grid and modified SIMPLE algorithm. A computer program in FORTRAN 90 is built to perform the numerical solution.The developed computational algorithm is tested for the flow over a flat plate (4m) long with uniform suction or blowing velocity ratios of (V/U∞ =± 0.0185, ± 0.0463 and ±0.0925 m/s) are imposed on the slot for Reynolds number of (1.36 x 107 ), based on the plate length. The position of the slot change in the range of (X/L=1/4, 1/2 and 3/4) from leading edge and also, change width of slot in the value equal (0.12, 0.2 and 0.28m).The plate temperature is (70 °C), with the free stream velocity and temperature are (8.6m/s) and (25 °C) respectively. In addition, the effects of pitch angles on the flow field are investigated in the range of (30о   150о).The numerical results show that, for a uniform blowing, location of slot equal (X/L=1/4) from leading edge, a significant reduction of skin friction coefficient, wall shear stress and boundary layer thickness [displacement and momentum] to occur. While, an increase in boundary layer shape factor. Reynolds stress (uv) is more decreased than [(uu) and (vv)], mean velocity profiles in wall coordinates and dimensionless distance (U+, y+) decreases. When slot location is moved downstream to locations (X/L=1/2 or 3/4) a similar behavior can be said and most effective slot is obtained as (slot at X/L= 3m) from leading edge. While width of slot equal (0.28m) is better than values equal (0.12m and 0.2m). An opposite observations for the case of suction. The numerical results are compared with available numerical results and experimental data and a satisfactory results are obtained.